Tata Kelola Pendapatan Parkir: Petugas Parkir Dishub dan Non Dishub - Zenna Millenia; Arif Farida (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2022)
Study this aim for knowing management parking income according to parking attendants at the transportation agency and non-dishub parking attendants in X City in effort enhancement Income Original Region of sector retribution parking in X City and obstacles management parking edge Street common in X City. Method study this use approach qualitative with type the research study descriptive . Informant study this consist party Service X City Transportation and Officers parking . Technique data collection is done with interview , observation and documentation. Results study could is known that management parking edge Street by Service X City Transportation has been belong to transparent because every information about parking edge Street could accessed by direct by public through website or come to office Service communication. Accountability management parking edge Street also full not quite enough answer because every officer service and interpreter parking given training and construction even supervision . Responsibility management parking by Service Communication also already good because every craftsman parking given attribute so that will is known interpreter parking below supervisor party service . Independence management parking seen moment take policy without interest private so as not each other harmful wrong one party . Activity monitoring of interpreter parking and take action interpreter trouble parking _ without there is difference treatment . Fairness parking management edge party service always notice interest officer field and Public based on principle equality and reasonableness.